Analisis Potensi Daya Tarik Wisata Air Terjun Wana Ayu Berbasis Unique Selling Point - Komang Winda Tarisa Dewi; Damiati Damiati; Luh Masdarini (Peneliti.net, 2026)
This study aims to describe the tourism potential of Wana Ayu Waterfall based on its Unique Selling Point (USP). The primary data were collected through direct observation and interviews with the site management and local community of Padangbulia village. The analysis employed in the study includes qualitative descriptive analysis. The research instruments consisted of observation sheets, interview guidelines, and documentation. The findings indicate that the Unique Selling Point of Wana Ayu Waterfall can be identified by analyzing the four tourism attraction components (4S). Something to See is reflected in the waterfall's pristine natural landscape and the distinctive sandstone rock formations, which create a unique and exotic geological attraction. Something to Do includes various recreational activities such as hiking, swimming, photography, and picnicking, supported by facilities that enhance visitors' comfort and safety. Something to Buy is represented by food and beverage stalls within the tourist area, as well as locally produced ground coffee from Padangbulia Village, which serves as a distinctive souvenir. Something to Learn is demonstrated through the historical discoveries and cultural remains found around Wana Ayu Waterfall, providing visitors with educational value and broader insights into the site's heritage. The analysis of these four components confirms that Wana Ayu Waterfall possesses a strong Unique Selling Point, which has the potential to enhance its attractiveness and increase tourist visitation. Keywords: Waterfall, Tourism Potential, 4S, Unique Selling Point